Translating with technology: How digitalisation affects authorship and copyright of literary texts - Koponen Maarit; Nyqvist Sanna; Taivalkoski-Shilov Kristiina (Routledge, 2022)
This chapter examines questions of copyright, authorship, and textual ownership in the context of literary translation, and particularly the effects of the increasing use of translation technology. Overall, translation is an anomaly in terms of copyright, which seeks to protect the expressions of original works rather than the ideas contained in them. Translations, however, are derivative works, where the ideas of the source text are expressed in a new form. Since the nineteenth century, copyright regimes have struggled to accommodate the moral and economic rights of the translator and the author of the original text. More recently, new complications have been introduced by technologies such as translation memories and machine translation, which are increasingly used in various domains. Such technological tools enable the reuse of translations as data, and machine translation in particular has the potential to extend this reuse to new contexts, including literary translation where translation technology has so far had less impact. The question of textual ownership becomes ambiguous in a technology-assisted translation process where a translator employs suggestions based on previous works. We examine the notions of textual ownership and authorship from legal, technical, and ethical perspectives, and we suggest possible solutions to the open questions.
Using Technologies for Creative-Text Translation